2019
DOI: 10.1136/bmjebm-2019-111244
|View full text |Cite
|
Sign up to set email alerts
|

How effective are ‘age’ tools at changing patient behaviour? A rapid review

Abstract: BackgroundA common form of risk communication is to relay the relative risk (%) of an adverse outcome based on surrogate markers associated with the outcome. A novel way of communicating risk is through ‘effective age’ of a person or specific organ. These tools can be used to change patient behaviour.ObjectiveTo determine the effect of ‘effective age’ tools on patient behaviour as compared with more traditional methods of risk communication.Study selectionWe performed a search of the PubMed database up to Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 21 publications
4
34
0
1
Order By: Relevance
“…''Biological age'' is an increasingly popular risk format that converts an absolute risk to a younger or older age by comparing risk factors to ideal or average levels, resulting in various labels such as real age, fitness age, heart age, lung age, kidney age, and bone age. 82,83 Age is a time-based concept, but biological age could also be conceptualized as an evaluative label or a relative risk, as it involves comparing a person's risk to ideal or average values. There is of particular interest in heart age, which is increasingly used around the world, 84 but the methods used to calculate these risk formats are highly variable: the same person may get a younger or older heart age depending on the model used and whether they are compared with ideal or average risk factors.…”
Section: Time-based Risk Formatsmentioning
confidence: 99%
“…''Biological age'' is an increasingly popular risk format that converts an absolute risk to a younger or older age by comparing risk factors to ideal or average levels, resulting in various labels such as real age, fitness age, heart age, lung age, kidney age, and bone age. 82,83 Age is a time-based concept, but biological age could also be conceptualized as an evaluative label or a relative risk, as it involves comparing a person's risk to ideal or average values. There is of particular interest in heart age, which is increasingly used around the world, 84 but the methods used to calculate these risk formats are highly variable: the same person may get a younger or older heart age depending on the model used and whether they are compared with ideal or average risk factors.…”
Section: Time-based Risk Formatsmentioning
confidence: 99%
“…Existing research on the effect of heart age calculators is divided into small experimental samples that were randomized (which show mixed results overall) [ 13 ] and large population samples where users have been simply described. This study aimed to draw these 2 areas together by reporting on the users of a new Australian heart age calculator, followed by lifestyle change outcomes in a smaller sample of users who signed up to receive a report and further support by email.…”
Section: Introductionmentioning
confidence: 99%
“…31 While there are claims that giving patients an 'older' heart age can motivate them to change their lifestyles, a review of biological age formats found no evidence that this is more effective than absolute risk formats. 32 Anecdotally, New Zealand GPs find this to be a useful communication tool to get people interested in their CVD risk and lifestyle change, but absolute risk must be used when considering medication. 33 This is important not only to determine who is at high risk and likely to benefit from medication, but also to enable a shared, informed decision with the patient.…”
Section: Communicationmentioning
confidence: 99%